Destination service quality, tourist satisfaction, tourist perceived value and tourist behavioural intention at Kuala Tahan National Park, Malaysia - Mohd Rahimi, Abdul Halim (2020)
Tourist behavioural intention research is a vital perspective in nature-based tourism destination that requires continuous efforts to identify factors that bring tourists back to destinations. Every destination has different features and characters to be offered for travellers to experiences the uniqueness of destinations to meet the needs and purpose of their visit. The lessening number of tourist arrival for the recent years to Taman Negara Kuala Tahan has giving impact towards local economic and affect various stakeholders operating their business at the destination. Therefore, the Stimulus Organism Response (SOR) theory is used to examine the relationship between destination service quality, tourist satisfaction, tourist perceived value and tourist behavioural intention in Taman Negara Kuala Tahan, Malaysia. This study applied a purposive sampling method and 350 respondents involved in this study. Structural Equation Modeling (SEM) with Partial Least Square (PLS) version 3.2.7 through second-order factor has been used to test the relationship and effect between the variables in this study. The findings found that the destination quality services have a positive relationship with the tourist satisfaction, tourist perceived value and negative relationship with the tourist behavioural intention. Tourist satisfaction as a mediating factor was found positive between destination service quality and tourist behavioural intention and the tourist perceived value as a moderating factor was found negative destination service quality and tourist behavioural intention. The results also show that the level of destination service quality, tourist satisfaction, tourist perceived value and the level of tourist behavioural intentions is high towards the destination. Based on the illustration of the compatibility of PLS 3.2.7 statistical analysis, the research findings provide useful information to understand more about the quality research of services in nature tourism that focus on the context of Taman Negara Malaysia. These findings also provide guidelines for tour operators, stakeholders and local authorities to manage the destinations from tourist perspectives to improve the level of service delivery in the destination.